Pengeringan Kakao Menggunakan Rumah Pengering Hybrid - Wisnumurti, Yogie Wiweka; Warji, Warji; Tamrin, Tamrin; Kuncoro, Sapto (abe.fp.unila.ac.id, 2023)
Cocoa (Theobroma cacao) is one of the plantation commodities in Indonesia that has an important role for the national economy to increase the country's foreign exchange. The process of cocoa drying will result in a dried product changes color, texture, and scent. The purpose of this study was to analyze the efficiency of drying cocoa using a hybrid dryer house with three treatments namely, drying using solar energy drying, drying using solar energy drying and gas energy (hybrid) and conventional drying. The results showed that drying cocoa in a drying house using solar energy takes 270 hours or 12 days, drying using a drying house using solar energy and gas (hybrid) takes 222 hours (9 days) and drying using a winch (conventional) takes 240 hours (11 days). Keywords: Cocoa, Drying, Hybrid Dryer House.